Difficult situations and critical life events their significance in the parenting roles of mothers - Puszcz, Paulina (Difficult situation in biographies: Volume 9, 2025)
Difficult situations and critical life events are significant biographical experiences for a person. Reflecting on them and interpreting their meaning in individuals’ lives can have educational, developmental, organizing, adaptive, and therapeutic value. The aim of this study was to reconstruct challenging biographical experiences that, from the perspective of mothers, were meaningful in fulfilling their parental role. The study was conducted among 15 women, aged 24 to 35, who are mothers. The analysis of the research results indicates that experiencing and interpreting difficult life situations and critical life events by the surveyed mothers revealed their importance in strengthening maternal identity, centralizing motherhood among other values, coping with difficulties, and strengthening the relationship with their child.